EL OCIO CONECTADO, MÓVIL, TRANSMEDIAY MULTISOPORTE DE LOS JÓVENES EN LA ERA DIGITAL - Dra. Rosalba MANCINAS-CHÁVEZ,Dr. Ramón REIG (Fonseca, Journal of Communication, 2023)
This article defends the need for transversality when methodologically addressing instant messaging via cellphones as a tool of communication from the point of view of social sciences and humanities. This leads us to the structural approach, which requires supplementary knowledge in fields such as Psychology or History, without losing sight that our study is composed in the areas of Communications and Journalism. We intend to avoid the functional approaches to think about the meaning of mobile phones as a communicative and palliative object of human loneliness